2006
DOI: 10.1001/jama.296.9.1055
|View full text |Cite
|
Sign up to set email alerts
|

Extended Work Duration and the Risk of Self-reported Percutaneous Injuries in Interns

Abstract: Extended work duration and night work were associated with an increased risk of percutaneous injuries in this study population of physicians during their first year of clinical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
249
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(268 citation statements)
references
References 19 publications
10
249
3
6
Order By: Relevance
“…Findings from the US National Postgraduate Medical Survey 42 indicate that, when compared with day shift work, night work was associated with double the risk (odds ratio, 2.04) of percutaneous injury (needle stick and lacerations) in first-year medical interns, injuries posing serious hazards of transmission of blood-borne pathogens. Nurses working nights also experience more fatigue, sleep disturbance, and disturbed mood, and have poorer sleep quality than do nurses who do not work night shifts.…”
Section: Personal Safetymentioning
confidence: 99%
“…Findings from the US National Postgraduate Medical Survey 42 indicate that, when compared with day shift work, night work was associated with double the risk (odds ratio, 2.04) of percutaneous injury (needle stick and lacerations) in first-year medical interns, injuries posing serious hazards of transmission of blood-borne pathogens. Nurses working nights also experience more fatigue, sleep disturbance, and disturbed mood, and have poorer sleep quality than do nurses who do not work night shifts.…”
Section: Personal Safetymentioning
confidence: 99%
“…General surgery had a significantly higher rate at 0.07 per internmonth, with only OBGYN interns at higher risk at nearly 0.1 per intern-month [4].…”
Section: Surgical Trainee-specific Riskmentioning
confidence: 92%
“…A study published in JAMA in 2006 looked specifically at interns and their risk of percutaneous injuries and found the mean rate per intern-month of percutaneous injuries to be approximately 0.03 [4]. General surgery had a significantly higher rate at 0.07 per internmonth, with only OBGYN interns at higher risk at nearly 0.1 per intern-month [4].…”
Section: Surgical Trainee-specific Riskmentioning
confidence: 99%
“…8 The topic is of importance as recent survey work demonstrated that nurses working >12 hours and resident-physicians working shifts of 24 of more hours make significantly more medical errors and suffer many more occupational injuries than those working less exhausting schedules. 4,5,[9][10][11][12] Objective data on resident-physicians has corroborated these findings, 13,14 but objective data measuring sleepiness in nurses has been lacking. Surani et al's study helps to fill this need.…”
Section: Improving Nurse Working Conditions: Towards Safer Models Of mentioning
confidence: 98%